2015
DOI: 10.1111/ajpy.12065
|View full text |Cite
|
Sign up to set email alerts
|

Be water: Direct and indirect relations between perceived emotional intelligence and subjective well‐being

Abstract: Trait emotional intelligence (TEI) has been shown to have predictive capacity for certain dimensions of adaptation, such as life satisfaction and affectivity. The Trait Meta Mood Scale (TMMS), based on the EI ability model, has been shown to have predictive capacity for subjective well-being through its three factors (attention, clarity, and emotional repair), but little is known about the mediating role played by these dimensions, both among themselves and in relation to other variables. The aim of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 41 publications
(85 reference statements)
3
25
0
22
Order By: Relevance
“…Thus, the mediating effects of Attention were in the opposite direction to those hypothesised. Others studies have found similar results (Vergara, Alonso‐Alberca, San‐Juan, Aldás, & Vozmediano, ). The negative effect of Attention could be explained by a form of emotional rumination: a repetitive self‐focus on negative aspects of the emotions.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, the mediating effects of Attention were in the opposite direction to those hypothesised. Others studies have found similar results (Vergara, Alonso‐Alberca, San‐Juan, Aldás, & Vozmediano, ). The negative effect of Attention could be explained by a form of emotional rumination: a repetitive self‐focus on negative aspects of the emotions.…”
Section: Discussionsupporting
confidence: 75%
“…Although a certain level of Attention is required for understanding and controlling emotions and so improving SWB (Lischetzke & Eid, ), it may be inferred that constant attention to one's emotions could be maladaptive. In fact, there is a great deal of research that has shown that rumination maintains NA (Vergara et al, ). Also, Attention may also play a role in depression such that depressed individuals may allocate too much attention to their emotions (Salovey, Mayer, Goldman, Turvey, & Palfai, ).…”
Section: Discussionmentioning
confidence: 99%
“…La IE ha sido relacionada con numerosas variables criterio. Presenta implicaciones sobre indicadores de ajuste, bienestar, salud, felicidad, personalidad (Mikolajczak et al, 2015;Rey, Extremera, & Pena, 2016;Vergara, Alonso-Alberca, San-Juan, Aldás, & Vozmediano, 2015) y se observa específicamente que mayores niveles en esta habilidad se relaciona con una mejor salud tanto física como mental, con un mayor bienestar, un mejor funcionamiento social y rendimiento escolar, menor agresividad, entre otros (Gutiérrez-Cobo, Cabello-González, & Fernández-Berrocal, 2017).…”
Section: Inteligencia Emocionalunclassified
“…These studies have shown a positive association between both variables in college students (Extremera, Salguero, & Fernández-Berrocal, 2011), adults (Vergara, Alonso-Alberca, San-Juan, Aldás, & Vozmediano, 2015), adolescents and primary school pupils (Ferragut & Fierro, 2012). Furthermore, there are studies that have found a relationship between PEI and life satisfaction in both young and adult people (Vergara et al, 2015), as in undergraduated students (Extre me ra, Durán, & Rey, 2009) and adolescent population (Rey, Extre me ra, & PERCEIVED EMOTIONAL INTELLIGENCE, SUBJECTIVE WELL-BEING, PERCEIVED STRESS, ENGAGEMENT AND ACADEMIC ACHIEVEMENT OF ADOLESCENTS 359 Revista de Psicodidáctica, 2016, 21(2), 357-374 Pena, 2011). Moreover, the results are consistent to show that the specific skills of emotional clarity and repair play a significant role in the subjective well-being Ferragut & Fierro, 2012;Rey et al, 2011;Vergara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are studies that have found a relationship between PEI and life satisfaction in both young and adult people (Vergara et al, 2015), as in undergraduated students (Extre me ra, Durán, & Rey, 2009) and adolescent population (Rey, Extre me ra, & PERCEIVED EMOTIONAL INTELLIGENCE, SUBJECTIVE WELL-BEING, PERCEIVED STRESS, ENGAGEMENT AND ACADEMIC ACHIEVEMENT OF ADOLESCENTS 359 Revista de Psicodidáctica, 2016, 21(2), 357-374 Pena, 2011). Moreover, the results are consistent to show that the specific skills of emotional clarity and repair play a significant role in the subjective well-being Ferragut & Fierro, 2012;Rey et al, 2011;Vergara et al, 2015). Studies addressing the relationship between perceived stress and PEI have also supported the existence of a negative relationship between these variables in adults and in undergraduated students (Augusto-Landa, López-Zafra, BerriosMartos, & Aguilar-Luzón, 2008) and college students (Extremera, Durán, & Rey, 2007).…”
Section: Introductionmentioning
confidence: 99%